1998
DOI: 10.1002/(sici)1097-0142(19980815)83:4<788::aid-cncr24>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production profiles in the peritoneal fluids of patients with malignant or benign gynecologic tumors

Abstract: BACKGROUND Cytokines play a key role in the regulation of cells of the immune system and also have been implicated in the pathogenesis of malignant diseases. Some cytokines have been shown to have potential in the diagnosis of cancer. METHODS A total of 111 patients with ovarian, cervical, or endometrial carcinomas or benign ovarian or uterine tumors were enrolled on the study, and the levels of interleukin (IL)‐2, IL‐4, IL‐6, IL‐10, interferon (IFN)‐γ, granulocyte‐colony stimulating factor (G‐CSF), granulocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…HPV-associated cervical cancer induces inflammatory response due to viral infection, resulting in potential increased macrophage infiltration and induction of cytokines (2,3). The presence and possible involvement of several chemokines and cytokines have been studied in cervical cancer; however, the molecular mechanisms involved in the disease process are still poorly elucidated (3).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…HPV-associated cervical cancer induces inflammatory response due to viral infection, resulting in potential increased macrophage infiltration and induction of cytokines (2,3). The presence and possible involvement of several chemokines and cytokines have been studied in cervical cancer; however, the molecular mechanisms involved in the disease process are still poorly elucidated (3).…”
Section: Introductionmentioning
confidence: 79%
“…One study found no difference in the expression of c-fms in cervical precancerous lesions and normal tissue; however, c-fms levels were not examined in cervical carcinomas (21). Several studies, one by our group, showed an increase in serum and peritoneal CSF-1 levels in cervical cancer patients compared with control (3,19,20). Combined, these studies raise an important question on whether cervical carcinomas c-fms and CSF-1 in Cervical Cancer www.aacrjournals.org express c-fms and CSF-1 and whether this expression is higher than in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These markers have been found to be capable of discriminating cervical cancer patients from those without malignant transformation. Comparable levels of these three cytokines (but without statistical significance), were observed in the study of Punnonen et al [23], although a different type of research material was used and the tested group of cervical cancer patients was much smaller (n = 23). Significant data for G-CSF has also been observed in www.fhc.viamedica.pl the studies of other authors who additionally confirmed auto -and/or paracrine growth stimulation of tumor cells by this cytokine in different histological types of cervical cancer: carcinosarcoma [24], small-cell [14] and squamous cell [11][12][13] carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this data contradicts that of Punnonen et al [23] who postulated that malignant and benign tumors generally induce similar levels of cytokine production. However, these authors compared (among other gynecological malignancies) cervical cancer patients with benign ovarian and uterine lesions patients only, and purely in peritoneal fluids [23].…”
Section: Discussionmentioning
confidence: 99%